2019
DOI: 10.48550/arxiv.1906.10323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wormholes without exotic matter in nonminimal torsion-matter coupling $f(T)$ gravity

Rui-Hui Lin,
Zhen-Yuan Wu,
Xiang-Hua Zhai

Abstract: Wormholes are hypothetical tunnels that connect remote parts of spacetime. In General Relativity, wormholes are threaded by exotic matter that violates the energy conditions. In this work, we consider wormholes threaded by nonexotic matter in nonminimal torsion-matter coupling f (T ) gravity. We find that the nonminimal torsion-matter coupling can indeed hold the wormhole open. However, from geometric point of view, for the wormhole to have asymptotic flatness, the coupling matter density must falloff rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is also observed that as we increase the value of parameter α, our wormhole solution avoids exotic matter (or avoid violation of WEC and NEC) and provides more appropriate solution of wormhole geometry. Due to the problematic nature of exotic matter, it is suggested to minimize the presence of exotic matter to make it appropriate for travelling [37,40,41]. We observe that exponential function violates the non-existence theorem and supports the wormhole formulation with less amount of exotic matter with the higher values of parameter α.…”
Section: A Anisotropic Fluidmentioning
confidence: 75%
See 1 more Smart Citation
“…It is also observed that as we increase the value of parameter α, our wormhole solution avoids exotic matter (or avoid violation of WEC and NEC) and provides more appropriate solution of wormhole geometry. Due to the problematic nature of exotic matter, it is suggested to minimize the presence of exotic matter to make it appropriate for travelling [37,40,41]. We observe that exponential function violates the non-existence theorem and supports the wormhole formulation with less amount of exotic matter with the higher values of parameter α.…”
Section: A Anisotropic Fluidmentioning
confidence: 75%
“…Due to the problematic nature of exotic matter, it is suggested to minimize the presence of exotic matter to make it appropriate for travelling [37,40,41]. In classical GR the wormhole geometry is supported by the presence of exotic matter that violates the NEC and WEC.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that obtained solution satisfies the weak and the null energy conditions at the throat and its vicinity. In this line of direction several solutions have been thoroughly analyzed for wormholes [68][69][70]. It should be stressed that, dynamical wormhole in f (T ) gravity was found in [71].…”
Section: Introductionmentioning
confidence: 99%